2009
DOI: 10.1080/02772240802541379
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of methylene blue from aqueous solution by chemically treated water hyacinth

Abstract: Water hyacinth (WH), an aquatic plant macrophyte, was investigated for its ability to perform as a suitable adsorbent for methylene blue (MB) from aqueous solution. The non-living biomass of WH was subjected to several chemical treatments, namely, washing with hot water, washing with hot dilute HCl, soaking in NaOH, soaking in HNO 3 , and sulfonation. The system variables studied also include pH and MB concentration. The Langmuir isotherm was found to represent the measured adsorption data well except for WH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
6
0
3
Order By: Relevance
“…3, it was observed that the uptake capacity was found to be increased with increase in contact time. The adsorption was a very fast process for the first 120 min, and then the rate decreased [11]. The uptake capacity of chromium increases as the concentration of Cr(VI) increases [6,12].…”
Section: Effect Of Initial Cr(vi) Concentrationmentioning
confidence: 97%
“…3, it was observed that the uptake capacity was found to be increased with increase in contact time. The adsorption was a very fast process for the first 120 min, and then the rate decreased [11]. The uptake capacity of chromium increases as the concentration of Cr(VI) increases [6,12].…”
Section: Effect Of Initial Cr(vi) Concentrationmentioning
confidence: 97%
“…Enceng gondok yang digunakan diperoleh dari Telaga Ngipik, Kabupaten Gresik, Jawa Timur, dimana telaga tersebut merupakan telaga hasil reklamasi lahan tambang bahan baku semen dan eceng gondok yang bersifat sebagai biosorben alami, sehingga sebelum digunakan sebagai adsoben diperlukan regenerasi adsorben eceng gondok. Perlakuan dengan menggunakan larutan asam seperti larutan HNO 3 (El-Khaiary, 2007), H 3 PO 4 (ElNabarawy dan Khedr, 2000) dan HCl (Shofiyani dan Gusrizal, 2006;Priya dan Selvan, 2014) umumnya digunakan untuk regenerasi adsorben eceng gondok. Pada penelitian ini, HCL digunakan untuk regenerasi adsorben eceng gondok karena HCl adalah yang paling banyak digunakan.…”
Section: Pendahuluanunclassified
“…Devido aos problemas decorrentes ambientais, muitos estudos associados a novas tecnologias têm sido propostos para o tratamento de efluentes têxteis, como por exemplo, a ozonização [11], fluxo subcrítico [12], degradação biológica [13], adsorção [14] e biossorção [15].…”
Section: Introductionunclassified